KETERBUKAAN ANTAR SAUDARA KANDUNG TENTANG SEKSUALITAS - Ayu Rahmadani, Lintang; Claretta, Dyva (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Generation Z tends to be more comfortable sharing personal experiences, including sexual behavior, through social media rather than with family members. However, sibling relationships have strong potential as a support system due to their equal, close, and emotionally connected nature. This study aims to analyze communication openness between siblings in disclosing sexual behavior among Generation Z individuals aged 17–27 years. The study employs interpersonal communication theory, particularly Julia T. Wood’s self-disclosure concept and the Johari Window model, to understand the dynamics of openness within sibling relationships. Using a qualitative phenomenological approach, data were collected through in-depth interviews with seven primary informants and three supporting informants in Surabaya during May 2026. Data validity was ensured through source triangulation. The findings show that communication about sexual behavior between siblings generally occurs face-to-face, spontaneously, and within everyday conversations. Disclosure is most common regarding relationships with the opposite sex, while discussions of sexual behavior remain largely within the hidden area of the Johari Window. Boundaries are commonly maintained regarding behaviors such as holding hands, hugging, kissing, and more intimate activities. The blind and unknown areas reveal that siblings can function as mirrors for self-reflection and personal understanding. Five key factors consistently influence communication openness: family communication climate, gender, age proximity, trust, and non-judgmental responses from siblings. The study concludes that openness in disclosing sexual behavior is selective and gradual, shaped by both relational and personal factors. A supportive family communication climate, mutual trust, non-judgmental interactions, and consistent communication strengthen the potential of siblings to serve as an effective support system.